Study on generation Y dining out behavior in Sabah, Malaysia - Marry Tracy Pawan; Juliana Langgat; Kamarul Mizal Marzuki (Center for Promoting Ideas (CPI), USA, 2014)
Dine out has become a famous trend which indirectly contribute to the booming of the foodservice industry in Malaysia. This trend has become one of the factors that need to be considered by the foodservice operators in order to enhance and maximize their sales. Apparently, this trend followed by most of the Generation Y’s generation. Generation Y dines out and spent more than older generations and they has become the key market segment in the food service industry. They are adventurous in trying new foods and places with their unique and bizarre eating habit. The purpose of this study is to explore the factors that influence the Generation Y to dine out. Moreover, this study also identify the popular spot of dine out places as well as the types of food service establishments. The analysis utilized a sample collected in Kota Kinabalu, Sabah, Malaysia involving convenience sampling with self-administered survey. In general, the group of Generation Y is choosing casual type of restaurant as one of their preferred destination to dine in. The findings of this study are discussed to assist the food service operators to expand their market segment into this emergence market by considering price , facilities and additional value for product offered by